Head dimensions of brahman and their crossbred bull spermatozoa are affected by cryopreservation - Rubio Guillén, Luis Jorge; Garde López-Brea, José Julián; Esteso, Milagros; Fernández Santos, María Rocío; González Villalobos, Decio Martín; Palomares Naveda, Roberto; Velarde, Juan Carlos; Madrid Bury, Ninoska; Soto Belloso, Eleazar; Quintero Moreno, Armando Arturo (Revista Científica de la Facultad de Ciencias Veterinarias)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> The objective of this study was to determine the effect of cryopreservation on morphometrics characteristic of Brahman and their crossbred bull sperm heads. Five ejaculates were collected from 4 bulls and diluted at 30°C in a skim milk-egg yolk extender. Two microscope slides were prepared from single extended sperm samples prior to freezing in nitrogen vapors, and another one after thawing, sperm smears were prepared as described above. All slides were air dried and stained with Hemacolor®. Sperm-head dimensions for a minimum of 150 sperm heads/samples were analysed from each sample by means of the Sperm-Class Analyser ® (SCA), and the mean measurements recorded. A GLM procedure was performed to evaluate the effect of cryopreservation on sperm head morphometric dimensions. Bull sperm heads were significantly (P<0.001) smaller in frozenthawed spermatozoa than in the extended samples for length (9.00 μm vs. 9.43 μm), width (4.82 μm vs. 5.13 μm), perimeter (32.46 μm vs. 33.69 μm) and area (36.20 μmô€€€ vs. 39.97 μmô€€€) for all bulls. Also, differences (P<0.001) were found within all bulls for whole morphometric parameters. The individual variability of sperm head measurements across all bulls ranged from 5.9% to 10.2% for fresh and thawed samples, respectively. In conclusion, the present study indicate that cryopreservation of bull semen did affect the morphometry to reduce the dimensions of Brahman and crossbred bull sperm heads. The differences among bulls may be indicative of the individual bull resistance to the cryopreservation process.